Neuroprotective Effects of Danshen Chuanxiongqin Injection Against Ischemic Stroke: Metabolomic Insights by UHPLC-Q-Orbitrap HRMS Analysis - Zhou, Peipei; Zhou, Lin; Shi, Yingying; Li, Zhuolun; Liu, Liwei; Zuo, Lihua; Zhang, Jun; Liang, Shuhong; Kang, Jian; Du, Shuzhang; Yang, Jing; Sun, Zhi; et al. (Frontiers in Molecular Biosciences, 2021)
The incidence of cerebral ischemic stroke characterized by high mortality is increasing every year. Danshen Chuanxiongqin Injection (DSCXQ), a traditional Chinese medicine (TCM) preparation, is often applied to treat cerebral apoplexy and its related sequelae. However, there is a lack of systematic research on how DSCXQ mediates its protective effects against cerebral ischemia stroke. Metabolomic analysis based on UHPLC-Q-Orbitrap HRMS was employed to explore the potential mechanisms of DSCXQ on ischemic stroke induced by transient middle cerebral artery occlusion (MCAO). Pattern analysis and metabolomic profiling, combined by multivariate analysis disclosed that 55 differential metabolites were identified between Sham group and Model group, involving sphingolipid metabolism, glycerophospholipid metabolism, phenylalanine, tyrosine and tryptophan biosynthesis, primary bile acid biosynthesis, pantothenate and CoA synthesis and valine, leucine and isoleucine biosynthesis pathways. DSCXQ could reverse brain metabolic deviations in stroke by significantly upregulating the levels of L-tryptophan, Lyso (18:0/0:0), LPC (18:2), Indole-3-methyl acetate, and downregulating the levels of sphinganine 1-phosphate, L-threonic acid, glutaconic acid and N6,N6,N6-Trimethyl-L-lysine. In our study, we focused on the neuroprotective effects of DSCXQ against neuroinflammatory responses and neuronal apoptosis on a stroke model based on sphingolipid metabolism. The expressions of Sphk1, S1PR1, CD62P, Bcl-2, Bax, and cleaved Caspase-3 in brain tissue were evaluated. The neurological deficit, cerebral infarct size and behavioral abnormality were estimated. Results showed that DSCXQ intervention significantly reduced cerebral infarct size, ameliorated behavioral abnormality, inhibited the expression of Sphk1, S1PR1, CD62P, Bax, Cleaved Caspase-3, while increased the level of Bcl-2, and prevented neuronal apoptosis. The limitations are that our study mainly focused on the verification of sphingolipid metabolism pathway in stroke, and while other metabolic pathways left unverified. Our study indicates that SphK1-SIP axis may potentiate neuroinflammatory responses and mediate brain damage through neuronal apoptosis, and DSCXQ could suppress the activity of SphK1-SIP axis to protect brain tissue in cerebral ischemia. In conclusion, this study facilitates our understanding of metabolic changes in ischemia stroke and the underlying mechanisms related to the clinical application of DSCXQ.